Physical activities and vo2 max: Indonesian national team, is there a difference before and after covid-19? - Ariestika, Elsa; Widiyanto, Widiyanto; Nanda, Fitri Agung (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2020)
Athletes must have high physical activity and optimal vo2max without experiencing fatigue, both for match performance or daily activities. This study aims to determine the level of physical activity and vo2max of Indonesian National Team athletes before and during the covid-19 pandemic. This research method using observational method using cross sectional design and analyzed using quantitative descriptive techniques. The sample in this study used purposive sampling of 30 athletes consisting of cricket, football, and volleyball athletes. The research instrument used the Global Physical Activity Questionnaire (GPAQ) questionnaire to determine physical activity, and the Bleep Test method to measure vo2max. The results showed that the athletes of the Indonesian National Team had physical activity with a high category of 80% and a moderate category of 20%. In the vo2max before covid -19, it showed a superior category of 50%, and at the time of covid-19, vo2max athletes experienced a similar decrease with the good category by 40%. This study concludes that the covid-19 outbreak is the single largest pandemic impacting the world. So that in the high physical activity of athletes, there is a difference in the vo2max of Indonesian national team athletes before and during the covid-19 pandemic.